Analyzing Russia’s Hybrid Warfare Strategy through HermeticWiper Against Ukraine: A Cybersecurity and Desecuritization Approach - Zulfian, Muhammad Haekal; Rahmadan, Yanuar (Indonesian Scientific Publication, 2025)
This study examines Russia’s deployment of HermeticWiper malware in the early hours preceding the 2022 full-scale invasion of Ukraine as part of a broader hybrid warfare strategy. Unlike conventional cyberattacks focused on espionage or financial gain, HermeticWiper was designed to irreversibly destroy digital infrastructure, disrupting governance, finance, and communication sectors. Using a qualitative case study method with secondary data from technical reports, academic literature, and verified media, the study finds that the malware was strategically aligned with military objectives. Despite the destructive intent, Ukraine demonstrated significant cyber resilience through formal institutional responses and collaborations with Microsoft, ESET, and its volunteer-based IT Army. The study applies the National Cybersecurity Strategy framework and Desecuritization Theory to highlight how Ukraine addressed the threat without escalating the conflict. These findings illustrate a paradigmatic shift in modern warfare, where digital domains play a central role in national defense.